2006
DOI: 10.1161/01.str.0000222937.30216.13
|View full text |Cite
|
Sign up to set email alerts
|

A Discriminative Prediction Model of Neurological Outcome for Patients Undergoing Surgery of Brain Arteriovenous Malformations

Abstract: Background and Purpose-To develop and validate a discriminative model for predicting neurological morbidity after brain arteriovenous malformation (bAVM) surgery. Methods-Of 233 consecutive, prospectively enrolled patients undergoing bAVM surgery, the first 175 were used to derive, and the last 58 to validate, the prediction model. Demographic and angiographic factors were related to modified Rankin Scale scores assigned before, within 72 hours, at 7 days and at Ն1 year after surgery to seek predictors of post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…The risks of treatment are not homogeneous where treatment strategies depend on characteristics of the lesion, availability of individual treatment modalities, and institutional expertise. 10,12,17,[31][32][33][34] Several retrospective series have recently been published on ubAVMs. The SIVMS (Scottish Intracranial Vascular Malformation Study) reported on ubAVMs comparing conservative management with intervention, which also found superiority in the conservative group for death or handicap at 4 years and focal neurological deficit or death at 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…The risks of treatment are not homogeneous where treatment strategies depend on characteristics of the lesion, availability of individual treatment modalities, and institutional expertise. 10,12,17,[31][32][33][34] Several retrospective series have recently been published on ubAVMs. The SIVMS (Scottish Intracranial Vascular Malformation Study) reported on ubAVMs comparing conservative management with intervention, which also found superiority in the conservative group for death or handicap at 4 years and focal neurological deficit or death at 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis (model C) restricted to the subset of cases included in model B found that the HR for Hispanics, 26 This may be explained by a fundamentally weaker association of anatomic factors with ICH or more likely because of variability in interpretation of imaging studies. [27][28][29] For example, Al-Shahi et al [27][28][29] studied descriptors determined by catheter angiography and found interobserver agreement ranging from 14% to 62%, generally worse for characteristics associated with more complex angioarchitecture. Of note was low interobserver agreement involving the measurement of Spetzler-Martin grade (47%) and the presence of aneurysms (40%), 2 variables that arguably bear some importance in patient management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies incorporating MRI findings found only modest improvement in interobserver agreement with kappas ranging from 38% to 90%. 28,29 Furthermore, we did not adjust for BAVM location or associated aneurysms in our multivariate model because these data were not available for KPMCP patients at the time of analysis, which may also explain some differences from previous natural history studies of BAVM.…”
Section: Discussionmentioning
confidence: 99%
“…26 Some series reported the lack of impact of size or eloquent location of AVMs on surgical outcome. 14,24 This may be explained by cohort surgical series that do not take into consideration patients at high risk because they have been excluded from surgical treatment. Davidson and Morgan attempted to account for the patients who had been excluded from surgical treatment and concluded that all the variables of the Spetzler-Martin grading system were of importance and that the Spetzler-Martin grading system was a reliable way of stratifying risks from surgery.…”
mentioning
confidence: 99%